Potential Analysis of Drug Interactions in Schizophrenia Cases At One of the Bandung District Pharmacy, Indonesia - Herliany, Yane Srie; Nurdin, Hari (International Journal of Global Operations Research, 2024)
Schizophrenia is a heterogeneous syndrome of thought disturbances, delusions, hallucinations, emotional disturbances, decreased cognitive function and disturbed psychosocial functions. Treatment of schizophrenia aims to prevent hospitalization, ensure the patient's symptoms are stable and independent such as work or school. The purpose of this study was to determine the potential for drug interactions in schizophrenia cases based on their mechanism of action and severity. This research method is a descriptive study using data collected retrospectively on prescription drug data sheets in the pharmacy. The collected data were analyzed quantitatively and qualitatively. The results of the study from a total of 133 prescriptions found potential drug interactions in 509 cases. Drug interactions based on the mechanism of action, pharmacodynamics were found in 494 cases and 15 cases of pharmacokinetic . Based on the level of severity, there were interactions with 15 cases of mild severity, 287 cases of moderate severity and 217 cases of severe severity